Modeling and Evaluation of Circular Layout Facility in Hospitals - Pillai, Sini V.; V. S., Abhilash (Prabandhan: Indian Journal of Management, 2022)
Hospitals encompass an intricate infrastructure with a broad collection of practical units of medical forces. A fine planned facility layout planning is necessary for the smooth performance, in addition, to affording protected and suitable services to patients at the exact point in time. The paper proposed an optimized new facility unidirectional circular pathway of patient movement for achieving better health outcomes. The proposed layout would effectively avoid face-to-face contact of arriving and leaving patients inside a hospital, thus maintaining social distancing to avoid the spread of diseases or infection and hurry up the service deliverance method. A qualitative study was conducted for observing various movements of patients and health service providers inside existing hospital layouts, and semi-structural interviews were conducted to identify various issues of the existing infrastructural layouts inside hospital settings. The performance metrics considered included time, the distance between patients at various interaction points, and the capacity of rooms. The proposed layout was compared with the spring layout and random layout to evaluate the efficiency of the proposed system. This circular design proves to be an extremely suggested design to ensure social distancing in a pandemic or during the spread of infectious diseases.